Mu killer-Mediated and Spontaneous Silencing of Zea mays Mutator Family Transposable Elements Define Distinctive Paths of Epigenetic Inactivation - Skibbe, David S.; Fernandes, John F.; Walbot, Virginia (Frontiers in Plant Science, 2012)
Mu killer contains a partial inverted duplication of the mudrA transposase gene and two copies of the terminal inverted repeat A (TIRA) region of the master MuDR element of maize. Mu killer can effectively silence single copy MuDR/Mu lines, and it is proposed that a ~4 kb hairpin RNA is generated by read-through transcription from a flanking gene and that this transcript serves as a substrate for siRNA production. Mu killer was sequenced, except for a recalcitrant portion in the center of the locus, and shown to be collinear with mudrA as originally proposed. The ability of the dominant Mu killer locus to silence a standard high copy number MuDR/Mu transposon line was evaluated. After two generations of exposure, about three quarters of individuals were silenced indicating reasonable effectiveness as measured by the absence of mudrA transposase transcripts. Mu killer individuals that effectively silenced MuDR expressed two short antisense transcripts. In contrast, Mu killer individuals that failed to silence MuDR expressed multiple sense transcripts, derived from read-through transcription initiating in a flanking gene, but no antisense transcripts were detected.